(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
The urn contained the burnt remains of an adult male aged 30-40 years who had suffered from mild spinal degeneration. The deposit was substantial and well preserved. A small quantity of immature sheep/goat was associated. All bone was well calcined.